Dreams and visions : is Jesus awakening the Muslim world? - Doyle, Tom, 1955-; Webster, Greg. (Nashville, Tenn. : Thomas Nelson, 2012)
What would you do if Jesus appeared to you and told you to follow Him-- and you're Muslim? Doyle has encountered a staggering number of Muslims who were first introduced to Jesus through a vision or dream so powerful that they eventually turned from their lifelong religion of Islam and embraced Christ as their Savior. Travel to the heart of the Middle East to meet new believers who have truly been touched by Jesus in the most miraculous way, through their nightly dreams.
Preface: Jesus and Muslims -- Egypt: Hosanna to the King of the Arabs -- Saudi Arabia: The forbidding nation -- Iran: Why Ahmadinejad can't sleep at night -- Jordan: Top honors in honor killings -- Intermission: The great awakening for Muslims -- Syria: Spies in the church -- Iraq: In the beginning, God created Iraq -- Israel, Gaza, and the West Bank: Walls still come down -- Afghanistan: The gates of Hell don't prevail -- America: Loving Muslims to Christ.
Includes bibliographical references.
Keywords: Christian converts from Islam -- Biography; Christianity and other religions -- Islam; Islam -- Relations -- Christianity; Interfaith relations; Nonfiction; Biographies